2023
DOI: 10.3390/ijms24054403
|View full text |Cite
|
Sign up to set email alerts
|

Lipids at the Nexus between Cerebrovascular Disease and Vascular Dementia: The Impact of HDL-Cholesterol and Ceramides

Abstract: Cerebrovascular diseases and the subsequent brain hypoperfusion are at the basis of vascular dementia. Dyslipidemia, marked by an increase in circulating levels of triglycerides and LDL-cholesterol and a parallel decrease in HDL-cholesterol, in turn, is pivotal in promoting atherosclerosis which represents a common feature of cardiovascular and cerebrovascular diseases. In this regard, HDL-cholesterol has traditionally been considered as being protective from a cardiovascular and a cerebrovascular prospective.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 162 publications
0
5
0
Order By: Relevance
“…Earlier we noted that vascular dementia is also linked to infection (35). Vascular dementia has similar characteristics to AD, PD, and LBD: the arteries contain plaque, and the epithelial cell lining of the arteries, veins, and capillaries are pigmented with melanin (91,92), which we theorize provides energy. We suggest researchers determine if the epithelial cells of individuals with vascular dementia have reduced melanin levels in the vasculature of their brains and/or heart or in the area of a deep vein thrombosis or other cardiac event that may have occurred, increased lipids, and mitochondrial dysfunction.…”
Section: Electrical Charge and Electromagnetic Synthesismentioning
confidence: 81%
“…Earlier we noted that vascular dementia is also linked to infection (35). Vascular dementia has similar characteristics to AD, PD, and LBD: the arteries contain plaque, and the epithelial cell lining of the arteries, veins, and capillaries are pigmented with melanin (91,92), which we theorize provides energy. We suggest researchers determine if the epithelial cells of individuals with vascular dementia have reduced melanin levels in the vasculature of their brains and/or heart or in the area of a deep vein thrombosis or other cardiac event that may have occurred, increased lipids, and mitochondrial dysfunction.…”
Section: Electrical Charge and Electromagnetic Synthesismentioning
confidence: 81%
“…Thus, the impact of HDL-cholesterol on cardiovascular health is not only dictated by its circulating levels, but also by the functionality of HDL particles, namely, their antioxidant, anti-inflammatory, and cholesterol efflux capacity, which are crucial for HDL lipoproteins to elicit their cardioprotective effects [8,9]. In line with this, an impairment in HDL-antioxidant, anti-inflammatory, and cholesterol efflux capacity is intimately linked with CVD [10][11][12][13][14][15]. In addition to HDL functionality, HDL-cholesterol distribution is also emerging as an important player in dictating the effect of HDL lipoproteins on cardiovascular health [16,17].…”
Section: Introductionmentioning
confidence: 94%
“…Studies have shown that calcium channel genes, autonomic nervous system abnormalities (increased norepinephrine) and increased cortisol are all associated with MVD and depression in hypertensive patients ( 45 , 46 , 48 ). Depressed patients frequently exhibit low levels of high-density lipoprotein cholesterol (HDL-C) and elevated triglyceride levels, both of which promote the growth of atherosclerosis, which is a key driver of vascular disease ( 49 ). In addition, autonomic nervous dysfunction and neurohormone imbalance, inflammatory reaction and hippocampal structural alterations are all significant factors that contribute to the complex and bidirectional association between DM and depression ( 40 , 50 ).…”
Section: Risk Factorsmentioning
confidence: 99%